Xylene biodegradation by free and immobilized Sphingomonas paucimobilis strain TY4-HX on graphene oxide - Hossein Mohammadpour; Mahdi Shahriarinour; Ramin Yousefi (علوم محیطی)
Introduction: In recent decades, xylene has been considered as one of the most important pollutants in soil, along with other aromatic compounds in crude oil and other petrochemicals. Therefore, the aim of this study was to find bacteria for the biodegradation of this compound and to increase the degradation efficiency of this compound with the help of immobilizing the bacterium on compounds with a nanostructure such as graphene oxide. Material and methods: In the current study, biodegradation of xylene by free and immobilized bacteria on graphene oxide was studied under optimized conditions. Isolated xylene degrading bacteria from contaminated soils were identified based on 16S rDNA gene sequencing and submitted to gene bank as Sphingomonas paucimobilis strain TY4-HX. Using response surface methodology, optimum values of pH, temperature and xylene concentration for xylene degradation by free and immobilized cells were determined as 7, 32ºC and 1.5g/l, respectively. Results and discussion: Free bacterial cells were able to degrade 45.8% of the xylene after 24h under optimized conditions. Analyzes by Fourier-transform infrared spectroscopy (FTIR) and Scanning Electron Microscope (SEM) showed that the strain adhered onto the Graphene oxide surface and developed a biofilm. Immobilized cells were able to degrade up to 86.3% of the xylene after 24h under optimized conditions. Conclusion: Our results indicated that free and immobilized Bacteria had a suitable application potential in the treatment of xylene-containing soils.